Development and validation of early death risk score model for emergency status prediction in very severe aplastic anemia - Liu, Xu; Yang, Wenrui; Zhang, Li; Jing, Liping; Ye, Lei; Zhou, Kang; Li, Yuan; Li, Jianping; Fan, Huihui; Yang, Yang; Xiong, Youzhen; Zhao, Xin; et al. (Frontiers in Immunology, 2023)
This study developed and validated the Early Death Risk Score Model for early identification of emergency patients with very severe aplastic anemia (VSAA). All 377 patients with VSAA receiving first-line immunosuppressive therapy (IST) were categorized into training (n=252) and validation (n=125) cohorts. In the training cohort, age >24 years, absolute neutrophil count ≤0.015×109/L, serum ferritin >900ng/mL and times of fever before IST >1 time were significantly associated with early death. Covariates were assigned scores and categorized as: low (score 0-4), medium (score 5-7) and high (score ≥8) risk. Early death rate was significantly different between risk groups and the validation cohort results were consistent with those of the training cohort. The area under the receiver operating characteristic curve for the model was 0.835 (0.734,0.936) in the training cohort and 0.862 (0.730,0.994) in the validation cohort. The calibration plots showed high agreement, and decision curve analysis showed good benefit in clinical applications. The VSAA Early Death Risk Score Model can help with early identification of emergency VSAA and optimize treatment strategies. Emergency VSAA with high risk is associated with high early death rate, and alternative donor hematopoietic stem cell transplantation could be a better treatment than IST even without HLA-matching.